(untitled) (Journal of Applied and Natural Science, 2015)
Three upland rice cultivars namely Vandana, Brown Gora and Kalinga collected from the Central Rainfed Upland Rice Research Station (CRURRS), Hazaribag, Jharkhand of the Central Rice Research Institute, are mycorrhiza sensitive genotypes. Their affinity towards mycorrhizal colonization varied. The cv. Kalinga had the highest colonization followed by Vandana and Brown Gora. Variation of arbuscular mycorrhizal fungi affinity of the rice genotypes might be due to the variable demands of phosphorus nutrition of the different genotypes. To justify these variable demands of phosphorus among these three cultivars of rice, four different doses of phosphorus (5, 10, 15 and 20 ppm) were imposed to them in a system of hydroponics. Overall, among the three cultivars, the highest uptake efficiency (34% at 30 days, 57% at 45 days, 68% at 60days and 70% at 75 days interval) throughout the growth period was noticed in the cv. Brown Gora, followed by Kalinga and Vandana. The physiological demands of phosphorus of these cultivars were finally estimated as the contribution of uptake phosphorus to the total dry matter production of the plants with respect to available phosphorus. The overall results of these estimations gave the highest value in cv. Kalinga followed by the cv. Vandana and Brown Gora. Therefore, the cultivars Brown Gora and Kalinga could be recommended for the cultivation of the vast upland rain-fed areas of the country for higher yield and increased phosphorus use efficiency which could ultimately contribute significantly to the food grain production of the country.